2013
DOI: 10.4238/2013.january.16.3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and description of a multiple sex chromosome system in Potamotrygon motoro (Chondrichthyes, Myliobatiformes) from the Paraná River, Argentina

Abstract: ABSTRACT. The Potamotrygonidae family represents the only freshwater group of specialized elasmobranchs and is composed of 4 genera: Plesiotrygon, Paratrygon, Potamotrygon, and Heliotrygon. Individuals of Potamotrygon motoro were collected from the Paraná River at Ituzaingó (Province of Corrientes) in Argentina. Mitotic preparations were obtained using direct techniques and lymphocyte cultures. Chromosomes were studied with conventional Giemsa, C-band and nucleolus organizer region stainings. The diploid numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The third, in P. aff. motoro and P. falkneri (Cruz et al , 2011) and in P. motoro (Aichino et al , 2013). Presently, the simple sex-determination systems were found in rays from the Amazon basin (Valentim et al , 2006; 2013; present study), whereas the multiple sex-determination system was found in rays from the Paraná basin (Cruz et al , 2011; Aichino et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The third, in P. aff. motoro and P. falkneri (Cruz et al , 2011) and in P. motoro (Aichino et al , 2013). Presently, the simple sex-determination systems were found in rays from the Amazon basin (Valentim et al , 2006; 2013; present study), whereas the multiple sex-determination system was found in rays from the Paraná basin (Cruz et al , 2011; Aichino et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In both freshwater and marine Batoidea, the constitutive heterochromatin was invariably located in the centromeric region of all the chromosomes, and the NORs were multiple (Stingo et al , 1995; Rocco et al , 2002; 2005; 2007; Valentim et al , 2006; 2013; Cruz et al , 2011; Aichino et al , 2013). This pattern was also found in the present study, although individuals of P. motoro from one locality (Jauaperi River) presented terminal heterochromatic blocks on the long arms of a single chromosome pair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely thought that the sex of chondrichthyans is also determined by the GSD system with XX/XY sex chromosomes 43,45 . In chondrichthyans, sex chromosomes have been reported for eight species when only those reports based on multiple individuals for both sexes are considered 15,25,[46][47][48][49] (Fig. 5, Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Considering all existing information and our data, we conclude that chondrichthyan karyotypes are generally characterized by numerous chromosomes (up to 106), with a large distribution of chromosome lengths in a karyotype, and sometimes include heteromorphic sex chromosomes. Most chondrichthyan species remain to be analysed, but this emerging karyotypic format is distinct from that of teleost fishes with relatively constant numbers (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) of chromosomes that often include homomorphic sex chromosomes 13,44 . The karyotype provides information about a species' inherent chromosome number and sizes, as well as centromere positions, and provides an ultimate goal of whole-genome sequence reconstruction.…”
Section: Discussionmentioning
confidence: 99%